Trajetórias pornográficas: O Riso pronto para o ataque, uma história dos jornais eróticos brasileiros - Azevedo, Natanael Duarte de (2015)
The presence of pornography in literature is considered as a category since the nineteenth century for its formal qualities which make it possible analysis that comprehend the intentionality of the insertion of pornographic text and/or its functionality in the literary genres. This second perspective makes it possible the study of the pornographic elements of satire that serves as an instrument for the critic to power. Supported by theoretical postulates of Hodgart (2010) and Frye (2014), according to which pornography serves as an instrument for the construction of satire, under the vision of the attack, we will analyze how pornography was taken as a satirical feature by the humorous and pornographic newspaper O Riso (1911-1912) in the Brazilian Belle Époque. To understand the production and circulation context of O Riso and how it incorporated pornography it is necessary to do a research by means of the methods proposed by Cultural History (CHARTIER, 1991 and 2007). According to Chartier, the history of reading and literature can only be made if the researcher take into account the practices and forms of reading, as well as ownership and representation of the discourse of a given time. We discuss here, more specifically, the pornographic and political discourses that constitute the newspaper O Riso in order to analyze the stress points and organization of those discourses in relation to the political critique restrained in the paper. We aim at understanding the pornographic discourse of the O Riso and its relation with the history of literature by means of the pornography and politics. We analyzed columns that deal with political and social issues as well as the pornographic novel “As Aventuras do Rei Pausolo” and other newspapers that had a direct dialogue with O Riso such as O Rio Nu (1898-1916), O Coió (1901-1902) and O Nabo (1900). The results of our analysis show that, by means of satire instruments and the different ways of appropriation of pornography, it is possible to see that the political criticism used pornography and, also, its inherent character that is the reader's excitement. The discourse that constitutes the newspaper O Riso it is not only the sexual one, but mainly its political positioning which was against the Republican government of Hermes da Fonseca.